ANALISIS KOMPONEN UTAMA DALAM SISTEM INFORMASI MANAJEMEN : KONSEP, FUNGSI, DAN IMPLEMENTASI - Marlina, Lenny; Safwandy Nugraha, Mulyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Management Information Systems (MIS) has evolved into one of the key components in the effective management of data and information in modern organizations. With advances in communication and information technology and the increasing complexity and volume of data faced by organizations, it is important to understand the key components of a SIM. The purpose of this research is to analyze the key components in SIM with a focus on the concept, function and implementation as SIM is not only a tool to collect and store data, but how it can contribute to strategic decision making. This research uses a qualitative approach through literature analysis and case investigations on several organizations that have successfully implemented SIM. Data was collected through in-depth interviews with managers and system users, as well as document analysis related to the use of SIM. The results showed that the success of SIM implementation is strongly influenced by four main components: understanding user needs, effective data integration, management support, and adequate training. This study also found that organizations that actively evaluate and adjust the system have a higher success rate in utilizing SIM. The impact of this research is expected to provide insight into the importance of understanding and implementing SIM components to achieve competitive advantage in business.